1999
DOI: 10.1001/archinte.159.17.2070
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing the Effect of Casein With That of Soy Protein Containing Varying Amounts of Isoflavones on Plasma Concentrations of Lipids and Lipoproteins

Abstract: Context: Isolated soy protein reduces plasma concentrations of total and low-density lipoprotein (LDL) cholesterol.Objective: To identify the agent(s) responsible for the cholesterol-lowering effect of soy in mildly hypercholesterolemic volunteers: isoflavones isolated together with soy protein or soy protein itself.Design: Double-blind randomized parallel trial.Setting: Single-center study.Participants: A total of 156 healthy men and women with LDL cholesterol levels between 3.62 mmol/L (140 mg/dL) and 5.17 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
246
4
12

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(272 citation statements)
references
References 41 publications
10
246
4
12
Order By: Relevance
“…Many of the trials included in the large metaanalysis of soy protein failed to lower LDL-C. Other recent trials have also not found differences between soy protein isolates and control proteins, mostly casein (Gardner et al, 2001;Teede et al, 2001). By contrast, Crouse et al (1999) showed a clear soy isoflavone-related effect on LDL-C. Despite the large number of subjects in that study, 156 women and men, there was no clear genderisoflavone interaction, since LDL-C lowering was of marginal significance in the postmenopausal women (P ¼ 0.07) and in the men; premenopausal women showed no change.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Many of the trials included in the large metaanalysis of soy protein failed to lower LDL-C. Other recent trials have also not found differences between soy protein isolates and control proteins, mostly casein (Gardner et al, 2001;Teede et al, 2001). By contrast, Crouse et al (1999) showed a clear soy isoflavone-related effect on LDL-C. Despite the large number of subjects in that study, 156 women and men, there was no clear genderisoflavone interaction, since LDL-C lowering was of marginal significance in the postmenopausal women (P ¼ 0.07) and in the men; premenopausal women showed no change.…”
Section: Discussionmentioning
confidence: 66%
“…The isoflavone content is likely to contribute strongly, since isoflavone-depleted soy protein appears less effective (Gardner et al, 2001;Wangen et al, 2001) and one large study has shown a dose-related effect when increasing amounts of isoflavones within soy protein were compared (Crouse et al, 1999). However, trials of purified isoflavones have to date been disappointing (Nestel et al, 1997(Nestel et al, , 1999Hodgson et al, 1998;Howes et al, 2000;Simons et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time, there was no recognition of a protective effect from isoflavones due to a paucity of data, but subsequent studies have shown that the cholesterollowering effect is influenced in a dose-dependent manner by the presence of isoflavones in the protein matrix [25,117]. Furthermore, data collected thus far in animals and from limited clinical trials show that isoflavones have protective or no effects on bone [8,29,62,93,100].…”
Section: Introductionmentioning
confidence: 99%